2014
DOI: 10.1089/apc.2014.0076
|View full text |Cite
|
Sign up to set email alerts
|

HIV Stigma Among Substance Abusing People Living with HIV/AIDS: Implications for HIV Treatment

Abstract: HIV-related stigma has a major impact on quality of life and health among people living with HIV and AIDS (PLWHA). This study examines demographic, mental health, behavioral, contextual, and HIV care-related correlates of HIV stigma among 503 substance abusing PLWHA. Stigma was measured with the HIV Internalized Stigma Measure which has four subscales: stereotypes about HIV, self-acceptance, disclosure concerns, and social relationships. Severe substance dependence (55.3%) and depression (54.7%) were associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 37 publications
5
33
0
1
Order By: Relevance
“…As our findings have shown, such attributions are not only felt by substance users with HIV but also expressed by health care providers, and the literature supports this contention [6,39,[41][42][43]. The literature also demonstrates how this discourse of agency can negatively impact the health and well-being of substance users with HIV and inhibit HIV prevention efforts [19,22,24,25,27,28,41]. Tackling such attributions of personal responsibility is thus paramount.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…As our findings have shown, such attributions are not only felt by substance users with HIV but also expressed by health care providers, and the literature supports this contention [6,39,[41][42][43]. The literature also demonstrates how this discourse of agency can negatively impact the health and well-being of substance users with HIV and inhibit HIV prevention efforts [19,22,24,25,27,28,41]. Tackling such attributions of personal responsibility is thus paramount.…”
Section: Discussionsupporting
confidence: 67%
“…Stigmatization in health care settings, in particular, has been found to be highly detrimental to the well-being of substance users with HIV [8,19]. In fact, anticipated or enacted stigmatizing reactions from health care professionals can inhibit both substance use dependence treatment and HIV care [8,20,21] through testing delays [22,23], treatment avoidance [19,24,25], late entry into care [24], non-disclosure of substance use and/or HIV status [19,21,26], and poor access to antiretroviral therapy [27], all of which also impede HIV prevention efforts [19,28]. It is therefore important to engage in efforts to reduce the stigmatization of substance users with HIV in health care settings, and to improve interactions between health care professionals and substance users with HIV.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, whereas Cardarelli et al [46], Rao et al [57], Sayles et al [53], and Tyer-Viola et al [51] all found significant univariate associations between stigma and self-reported adherence among PLWH, these associations diminished to non-significance at the multivariate level, with other factors including mental health symptoms, depressive symptoms, and perceived general health status emerging as significant predictors. In another investigation [52], a combined stigma measure composed of four subscales (i.e., stereotypes of HIV, disclosure concerns, renegotiating social relationships, self-acceptance) was associated with adherence in univariate analyses, but adherence failed to predict any of the individual stigma subscales at the multivariate level. Instead, depression, social support, and attitudes toward providers and antiretroviral medications emerged as significant predictors of many of these stigma subscales.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 93%
“…The most frequently used measure was an original or modified version of Berger's HIV Stigma Scale [46][47][48][49][50][51], which includes four subscales of personalized stigma, disclosure concerns, negative self-image, and concern with public attitudes. In other investigations, stigma was assessed through a variety of instruments including the HIV Internalized Stigma Measure [52,53], HIV/AIDS Stigma Instrument-PLWA [54], Self-Stigma Scale [55], HIV/AIDS-related Stigma and Discrimination [56], Stigma Scale for Chronic Illness [57], and items selected from the Patient Medication Adherence Questionnaire [52]. These instruments are characterized by a range of subconstructs, including internalized (e.g., negative self-perception), anticipated (e.g., renegotiating social relationships), and enacted (e.g., healthcare discrimination) stigmas.…”
Section: Studies That Combined Multiple Dimensions Of Stigmamentioning
confidence: 99%
“…Rajabiun and colleagues (1993) found that stigma or perceived level of social acceptance after diagnosis presented as a barrier to engaging in routine medical services. Several stigma-related studies have been conducted with sub-populations disparately affected by HIV, including men who have sex with men, homeless individuals, substance users, and women (Berger, 2005;Levi-Minzi & Surratt, 2014;Semple, Strathdee, Zians, & Patterson, 2012;Wolitski, Pals, Kidder, Courtenay-Quirk, & Holtgrave, 2009). However, no empirical studies have specifically looked at the intersection of HIV stigma with incarceration stigma among African American men.…”
Section: Hiv-related Stigmamentioning
confidence: 99%